A low-density high-strength carbon / carbon composite material and a method for preparing the same

CN123003307APending Publication Date: 2026-10-30NORTHWESTERN POLYTECHNICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611214007.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,碳/碳复合材料的力学性能高度依赖于预制体结构、致密化工艺和最终机械加工方式,现有主流制备路线往往需经过多轮致密化循环,每一次循环均可能在纤维-基体界面引入热失配残余应力,对于厚度通常不足5 mm甚至仅1~2 mm的件而言,残余应力在厚度方向缺乏缓冲空间,容易导致微裂纹萌生和扩展,显著降低材料的表观强度和断裂韧性

Benefits of technology

本发明所述低密度高强度碳/碳复合材料及其制备方法在具体操作时,采用以浸渍热固性树脂的PAN基碳纤维布为预制体并结合放电等离子烧结(SPS)快速致密化的技术,针对性解决传统碳/碳复合材料的力学性能高度依赖于预制体结构、致密化工艺和最终机械加工方式,使传统碳/碳复合材料在大尺寸、异形化的高承载结构件应用中长期面临强度不足的技术困境。传统碳/碳复合材料试样的拉伸、弯曲和层间剪切强度相比未加工状态往往下降30%~50%以上。特别是层间剪切强度,结构中纤维铺层间的结合本就薄弱,典型值通常仅为10~20 MPa,一旦受到切削振动或局部热损伤,极易诱发层间分层,导致构件在服役过程中的突发性剥离失效。而本发明优化了纤维/基体界面结合状态,在整体密度低于1.40g/cm³的低密度区间内实现了基体碳的均匀、深层次填充,构建出连续、强结合的碳基体网络,将低密度碳/碳复合材料的弯曲强度提升至250 MPa以上,实现了低密度、高强度的统一。同时本发明兼具工艺周期短、成品率高的优点,制备工艺高效、可控,适合批量生产低密度高强度碳/碳复合材料,在航空发动机火焰筒、导弹弹头舵翼、高温热防护蒙皮等领域具有显著的实用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003307A_ABST
    Figure CN123003307A_ABST
Patent Text Reader

Abstract

The application discloses a kind of low-density high-strength carbon / carbon composite material and preparation method thereof, comprising the following steps: 1) PAN-based carbon cloth is cut into carbon cloth, and after ultrasonic cleaning, it is dried, after the carbon cloth after drying is treated by nitric acid acidification, then it is ultrasonic cleaned and dried again, to obtain treated carbon cloth;2) the treated carbon cloth is impregnated by polyimide solution treatment, and after solidification and drying, polyimide reinforced carbon / carbon composite material is obtained;3) polyimide reinforced carbon / carbon composite material is stacked to target thickness and placed into mold, and after discharge plasma sintering treatment, low-density high-strength carbon / carbon composite material is obtained, and the composite material obtained by the method has the characteristics of low density and high strength, and the mechanical properties are relatively excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite material preparation technology, and relates to a low-density, high-strength carbon / carbon composite material and its preparation method. Background Technology

[0002] Carbon / carbon composites are high-performance composite materials with carbon fibers and their fabrics as reinforcement and pyrolytic carbon or resin-based carbon materials as the matrix. Since their emergence in the late 1950s, they have occupied an irreplaceable position in aerospace, military equipment, and high-end civilian fields due to their unique performance advantages. This material combines many properties of graphite with superior characteristics compared to graphite, including lighter weight, better ablation resistance, superior thermal shock resistance, higher damage tolerance, and higher high-temperature strength retention. It can simultaneously achieve multiple functions such as electrical conductivity, thermal conductivity, thermal insulation, and heat preservation. These comprehensive advantages in lightweighting, high temperature resistance, thermal shock resistance, and friction reduction and wear resistance have made carbon / carbon composites recognized as one of the most promising ultra-high temperature structural materials, and they have been widely used in key areas such as solid rocket engine nozzles, space shuttle thermal protection structures, aircraft braking systems, hot-end components of aero engines, and photovoltaic thermal field materials.

[0003] The superior performance of carbon / carbon composites relies on their complex preparation processes. Currently, the mainstream densification processes include chemical vapor infiltration (CVI), liquid phase impregnation carbonization (PIP), and molding processes, with CVI holding a dominant position. CVI uses hydrocarbon gases such as methane and propane as carbon source precursors, pyrolyzing the gas at high temperatures to deposit a pyrolytic carbon matrix within the pores of the carbon fiber preform. This process causes no mechanical damage to the fibers, effectively maintaining the integrity of the reinforcement structure and high strength. Simultaneously, the carbon matrix does not shrink during deposition, resulting in good interfacial bonding. However, CVI is controlled by gas diffusion, leading to a slow deposition rate and production cycles typically ranging from hundreds to thousands of hours. The densification effect of a single application is limited, and it is difficult to completely eliminate closed pores, resulting in products with low density and a tendency to develop density gradients. For example, Chinese patent publication number CN119372567A discloses a 2.5D woven carbon fiber preform reinforced Zr-based composite material and its preparation method. This method uses 2.5D woven carbon fiber preforms as reinforcement, prepares solutions using ceramic particles and resin as raw materials, and then impregnates low-density C / PyC composites with a resin / ceramic solution. A dense Zr-based composite is then prepared through impregnation-carbonization-reactive infiltration. However, the composites prepared by this method have a high residual metal content, affecting their high-temperature performance. Chinese patent CN119263864A discloses a multi-scale three-dimensional network carbon skeleton structure-assisted composite material and its preparation method. This method impregnates low-density needle-punched fiber preform composites in a precursor solution, followed by curing-carbonization-reactive infiltration to prepare ceramic-modified composites. The precursor solution is a mixture of resorcinol, formaldehyde solution, distilled water, and hexadecyltrimethylammonium bromide. This method can reduce residual metals in the composite material, but it is costly, requires the use of toxic precursor solutions during preparation, pollutes the environment, and poses safety hazards. Liquid-phase impregnation carbonization uses phenolic resin, thermosetting resin, or coal tar pitch as impregnating agents. Through cyclic processes of impregnation, curing, and carbonization, the carbon matrix gradually fills the pores of the preform. This process is suitable for preparing components with complex shapes and relatively simple equipment requirements. However, it requires several or even more than ten impregnation-carbonization cycles to achieve the target density, and the densification efficiency is also limited. In the resin impregnation process, the gaseous products generated by resin decomposition easily escape along the fiber surface, weakening the interfacial bond between the fiber and the matrix. Furthermore, the carbonized resin forms amorphous carbon that is difficult to graphitize. The pitch impregnation process has a higher residual carbon rate and less damage to the fibers, yielding easily graphitized matrix carbon and more uniform and dense products. However, it requires strict purity of the pitch and is difficult to control impurities. Compression molding is mainly suitable for carbon / carbon composites reinforced with chopped fibers. Products are prepared by compression molding followed by carbonization. Although it can produce dense and uniform products, the product size is limited and anisotropy is a significant issue.In addition, carbon / carbon composites also face problems such as high energy consumption, low raw material utilization, and residual stress caused by the difference in thermal expansion coefficients between the matrix carbon and the fiber during the cyclic densification process. These factors together have led to the persistently high manufacturing cost of carbon / carbon composites.

[0004] The current state of research and application of carbon / carbon composites in terms of mechanical properties presents a contradictory characteristic of high specific strength coexisting with typical brittle fracture. Due to the excellent specific modulus and specific strength imparted by carbon fiber reinforcement, components can withstand high structural loads while meeting lightweight requirements, and their strength retention rate with increasing service temperature is far higher than that of metallic and ceramic materials. However, the mechanical properties of carbon / carbon composites are highly dependent on the preform structure, densification process, and final machining method. Current mainstream preparation routes often require multiple densification cycles, each of which may introduce thermal mismatch residual stress at the fiber-matrix interface. For components with a thickness typically less than 5 mm or even only 1–2 mm, the residual stress lacks buffer space in the thickness direction, easily leading to the initiation and propagation of microcracks, significantly reducing the material's apparent strength and fracture toughness. Furthermore, when using traditional machining methods to shape or drill carbon / carbon composites, the cutting tool cuts a large number of continuous carbon fibers across the machining area, severely disrupting the original fiber-based mechanical reinforcement mechanism. The tensile, flexural, and interlaminar shear strengths of the specimens often decrease by 30%–50% or more compared to the unprocessed state. In particular, interlaminar shear strength is a significant concern. The bonds between fiber layups in a structure are inherently weak, typically only 10–20 MPa. Once subjected to cutting vibrations or localized thermal damage, delamination is easily induced, leading to sudden peeling failure of the component during service. These dispersed mechanical properties and weak interface issues have resulted in insufficient strength for existing carbon / carbon composite materials in high-load-bearing structural applications, becoming a key bottleneck restricting their large-scale engineering applications in fields such as aero-engine flame tubes, missile warhead fins, and high-temperature thermal protective skins. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a low-density, high-strength carbon / carbon composite material and its preparation method. The composite material obtained by this method has the characteristics of low density and high strength, and has excellent mechanical properties.

[0006] To achieve the above objectives, this invention discloses a method for preparing a low-density, high-strength carbon / carbon composite material, comprising the following steps: 1) Cut PAN-based carbon cloth into carbon cloth, ultrasonically clean and dry it. Then, acidify the dried carbon cloth with nitric acid, ultrasonically clean it and dry it again to obtain the treated carbon cloth. 2) The treated carbon cloth is impregnated with a polyimide solution, cured and dried to obtain a polyimide-reinforced carbon / carbon composite material; 3) After the polyimide-reinforced carbon / carbon composite material is stacked to the target thickness, it is placed in a mold and subjected to spark plasma sintering to obtain a low-density, high-strength carbon / carbon composite material.

[0007] Furthermore, in step 1), the ultrasonic cleaning time for both times is 5 min-30 min, and the drying is done in an oven at 60℃-100℃.

[0008] Furthermore, the solvent in the polyimide solution is one or a combination of several of the following: isopropanol, deionized water, methanol, ethanol, propanol, n-butanol, isobutanol, n-hexane, n-pentanol, and isopentanol.

[0009] Furthermore, the mass ratio of polyimide resin to solvent in the polyimide solution should be 1:(1-10). Furthermore, the impregnation is carried out under normal pressure or under vacuum, and the impregnation process ends when there are no more bubbles.

[0010] Furthermore, when vacuum impregnation is used, the pressure is 0.01-10 kPa.

[0011] Furthermore, in step 2), during the curing and drying process, the standing time is 0.5-2 hours, the curing temperature is 60-90℃, the curing time is 48-72 hours, the drying temperature is 60-90℃, and the drying time is 12-36 hours.

[0012] Furthermore, in the discharge plasma sintering process, the heating rate is 80-250℃ / min, the final sintering temperature is 1600-2000℃, the holding time is 10-60min, the cooling rate is 10-60℃ / min, and the axial pressure is 10-50MPa.

[0013] Furthermore, the carbon cloth is circular.

[0014] This invention discloses a low-density, high-strength carbon / carbon composite material, which is prepared based on the preparation method of the low-density, high-strength carbon / carbon composite material.

[0015] The present invention has the following beneficial effects: The low-density, high-strength carbon / carbon composite material and its preparation method described in this invention employ a preform of PAN-based carbon fiber cloth impregnated with thermosetting resin, combined with rapid densification via spark plasma sintering (SPS). This method specifically addresses the problem that the mechanical properties of traditional carbon / carbon composite materials are highly dependent on the preform structure, densification process, and final machining method, leading to the long-standing technical dilemma of insufficient strength in large-size, irregularly shaped, high-load-bearing structural components. The tensile, flexural, and interlaminar shear strengths of traditional carbon / carbon composite samples often decrease by 30% to 50% or more compared to their unprocessed state. In particular, the interlaminar shear strength is significantly reduced; the bond between fiber layers in the structure is inherently weak, typically only 10–20 MPa. Once subjected to cutting vibration or localized thermal damage, delamination is easily induced, leading to sudden peeling failure of the component during service. This invention optimizes the fiber / matrix interface bonding, achieving uniform and deep-layer filling of matrix carbon within a low-density range (below 1.40 g / cm³), constructing a continuous and strongly bonded carbon matrix network. This enhances the flexural strength of the low-density carbon / carbon composite material to over 250 MPa, achieving a balance between low density and high strength. Furthermore, this invention boasts advantages such as short processing cycle and high yield, with an efficient and controllable manufacturing process suitable for mass production of low-density, high-strength carbon / carbon composite materials. It has significant practical value in fields such as aero-engine flame tubes, missile warhead fins, and high-temperature thermal protection skins. Attached Figure Description

[0016] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the description of the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 A cross-sectional electron microscope image of the carbon / carbon composite material prepared in this invention; Figure 2 This is a schematic diagram illustrating the preparation process and principle of the present invention; Figure 3 This is a force-displacement curve of the carbon / carbon composite material obtained in Example 1 of the present invention; Figure 4 This is a force-displacement curve of the carbon / carbon composite material obtained in Comparative Example 1 of the present invention. Detailed Implementation

[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] In the description of this invention, it should be understood that the terms "comprising" and "including" indicate the presence of the described features, integrals, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integrals, steps, operations, elements, components and / or collections thereof.

[0020] It should also be understood that the terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. As used in this specification and the appended claims, the singular forms “a,” “an,” and “the” are intended to include the plural forms unless the context clearly indicates otherwise.

[0021] It should also be further understood that the term "and / or" as used in this specification and the appended claims refers to any combination and all possible combinations of one or more of the associated listed items, and includes such combinations. For example, A and / or B can represent three cases: A alone, A and B simultaneously, and B alone. Additionally, the character " / " in this invention generally indicates that the preceding and following objects have an "or" relationship.

[0022] It should be understood that although terms such as first, second, third, etc., may be used in the embodiments of the present invention to describe the preset range, these preset ranges should not be limited to these terms. These terms are only used to distinguish the preset ranges from one another. For example, without departing from the scope of the embodiments of the present invention, the first preset range may also be referred to as the second preset range, and similarly, the second preset range may also be referred to as the first preset range.

[0023] Depending on the context, the word "if" as used here can be interpreted as "when," "when," "in response to determination," or "in response to detection." Similarly, depending on the context, the phrase "if determination" or "if detection (of the stated condition or event)" can be interpreted as "when determination," "in response to determination," "when detection (of the stated condition or event)," or "in response to detection (of the stated condition or event)."

[0024] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0025] The accompanying drawings illustrate various structural schematic diagrams according to embodiments disclosed in this invention. These drawings are not to scale, and some details have been enlarged for clarity, and some details may have been omitted. The shapes of the various regions and layers shown in the drawings, as well as their relative sizes and positional relationships, are merely exemplary and may deviate from reality due to manufacturing tolerances or technical limitations. Furthermore, those skilled in the art can design regions / layers with different shapes, sizes, and relative positions as needed.

[0026] refer to Figure 2 The preparation method of the low-density high-strength carbon / carbon composite material of the present invention includes the following steps: 1) Cut PAN-based carbon cloth into neat circular pieces, ultrasonically clean and dry them, then acidify the dried carbon cloth with nitric acid, ultrasonically clean and dry it again to obtain the treated carbon cloth. 2) The treated carbon cloth obtained in step 1) is impregnated with polyimide to obtain a polyimide-reinforced carbon / carbon composite material.

[0027] It should be noted that the present invention does not have any special requirements regarding the source of the polyimide resin; commercially available polyimide resin can be used. In the present invention, the polyimide resin can be, for example, a common commercial-grade polyimide resin. In the present invention, during impregnation, the impregnation solution is sufficient to completely submerge the material to be impregnated. Taking the impregnation of PAN-based carbon cloth with polyimide resin as an example, during impregnation, the amount of polyimide resin solution used is sufficient to completely submerge the PAN-based carbon cloth. 3) After the polyimide-reinforced carbon / carbon composite material is laminated to the target thickness, it is placed in a mold and then subjected to spark plasma sintering to obtain a low-density, high-strength carbon / carbon composite material.

[0028] The employed spark plasma sintering method generates spark plasma by directly introducing pulsed current between preforms, inducing Joule heating within the sintered body to drive rapid sintering and solidification. The heating rate in spark plasma sintering is 80-250℃ / min, the final sintering temperature is 1600-2000℃, and the holding time is 10-60 min; the cooling rate is 10-60℃ / min; and the axial pressure is 10-50 MPa.

[0029] It should be noted that this invention is the first to employ PAN-based carbon fiber cloth impregnated with thermosetting resin as a preform, combined with rapid densification technology via spark plasma sintering, overcoming the problems of lengthy repeated impregnation-carbonization cycles and the difficulty in simultaneously achieving low density and high strength in traditional carbon / carbon composite material preparation. The preparation process in this invention is efficient and controllable, suitable for mass production of low-density, high-strength carbon / carbon composite materials. The carbon / carbon composite material obtained by this invention has low density, high specific strength, and good interfacial bonding between the fiber and the pyrolytic carbon matrix. This invention completes resin carbonization and matrix densification in a single step during spark plasma sintering of the resin-impregnated PAN-based carbon cloth. Through the path proposed for the first time in this invention—using impregnated PAN-based carbon cloth as a reinforcing skeleton combined with rapid sintering via spark plasma sintering—a low-density, high-strength carbon / carbon composite material was designed and prepared, broadening the application of traditional carbon / carbon composite materials in aerospace lightweight components and other fields. The raw materials of this invention are readily available, the carbonization and densification processes are rapid and controllable, the preparation method is simple, the preparation cycle is significantly shortened, and it is easy to industrialize.

[0030] Example 1 This embodiment provides a method for preparing a low-density, high-strength carbon / carbon composite material, including the following steps: 1) Cut PAN-based carbon cloth into neat circular pieces, ultrasonically clean and dry them, then acidify the dried carbon cloth with nitric acid for 1 hour, ultrasonically clean and dry it again. 2) Prepare the polyimide solution. The carbon cloth treated in step 1) is impregnated with polyimide. Mix 70g of polyimide resin with 420g of anhydrous ethanol solution and stir evenly to obtain the impregnation polyimide solution. Put the laminated PAN-based carbon cloth into it and vacuum impregnate for 1 hour. Then put it into a 70℃ oven for curing for 3 hours. Repeat the impregnation process 10 times to obtain polyimide-reinforced carbon / carbon composite material. 3) After the polyimide-reinforced carbon / carbon composite material is stacked to the target thickness, it is placed in a spark plasma sintering mold. During the spark plasma sintering process, the heating rate is 100℃ / min, the final sintering temperature is 1900℃, the holding time is 30min, the cooling rate is 60℃ / min, and the axial pressure is 30MPa. After spark plasma sintering, a low-density high-strength carbon / carbon composite material is obtained.

[0031] The resulting low-density, high-strength carbon / carbon composite material exhibits a clear and complete interlaminar reinforcement structure. The composite material has a density of 1.35 g / cm³, a flexural strength of 250 MPa, and a force-displacement curve as shown below. Figure 3 As shown.

[0032] Example 2 This embodiment provides a method for preparing a low-density, high-strength carbon / carbon composite material, including the following steps: 1) Cut PAN-based carbon cloth into neat circular pieces, ultrasonically clean and dry them, then acidify the dried carbon cloth with nitric acid for 1 hour, ultrasonically clean and dry it again. 2) Prepare the 2123 thermosetting resin solution. Impregnate the carbon cloth treated in step 1) with the 2123 thermosetting resin. Mix 70g of 2123 thermosetting resin with 420g of anhydrous ethanol solution and stir evenly to obtain the 2123 thermosetting resin solution for impregnation. Put the laminated PAN-based carbon cloth into it and vacuum impregnate for 1 hour. Then put it into a 70℃ oven for curing for 3 hours. Repeat the impregnation process 10 times to obtain the 2123 thermosetting resin reinforced carbon / carbon composite material. 3) After the 2123 thermosetting resin reinforced carbon / carbon composite material is laminated to the target thickness, it is placed in a spark plasma sintering mold. During the spark plasma sintering process, the heating rate is 100℃ / min, the final sintering temperature is 1700℃, the holding time is 30min, the cooling rate is 60℃ / min, and the axial pressure is 30MPa. After spark plasma sintering, a low-density high-strength carbon / carbon composite material is obtained.

[0033] The resulting low-density, high-strength carbon / carbon composite material has a clear and complete interlaminar reinforcement structure. The composite material has a density of 1.4 g / cm3 and a flexural strength of 190 MPa.

[0034] Comparative Example 1 This comparative example provides a method for preparing carbon / carbon composite materials, including the following steps: 1) Cut PAN-based carbon cloth into neat circular pieces, ultrasonically clean and dry them, then acidify the dried carbon cloth with nitric acid for 1 hour, ultrasonically clean and dry it again. 2) Prepare the polyimide solution. The carbon cloth treated in step 1) is impregnated with polyimide. Mix 70g of polyimide resin with 420g of anhydrous ethanol solution and stir evenly to obtain the impregnation polyimide solution. Put the laminated PAN-based carbon cloth into it and vacuum impregnate for 1 hour. Then put it into a 70℃ oven for curing for 3 hours. Repeat the impregnation process 10 times to obtain polyimide-reinforced carbon / carbon composite material. 3) After laminating polyimide-reinforced carbon / carbon composite materials, the layers were placed in a spark plasma sintering mold. The heating rate during spark plasma sintering was 100℃ / min, the final sintering temperature was 1700℃, and the holding time was 30min. The cooling rate was 60℃ / min, and the axial pressure was 30MPa. After spark plasma sintering, carbon / carbon composite materials were obtained.

[0035] The final low-density, high-strength carbon / carbon composite material has a density of 1.38 g / cm³, a flexural strength of 90 MPa, and a force-displacement curve as shown below. Figure 4 As shown.

[0036] Comparative Example 2 This comparative example provides a method for preparing carbon / carbon composite materials, including the following steps: 1) Cut PAN-based carbon cloth into neat circular pieces, ultrasonically clean and dry them, then acidify the dried carbon cloth with nitric acid for 1 hour, ultrasonically clean and dry it again. 2) Prepare a 2123 thermosetting resin solution. Impregnate the carbon cloth treated in step 1) with the 2123 thermosetting resin. Mix 70g of 2123 thermosetting resin with 420g of anhydrous ethanol solution and stir evenly to obtain the 2123 thermosetting resin solution for impregnation. Place the laminated PAN-based carbon cloth into it and vacuum impregnate for 1 hour. Then place it in a 70℃ oven for curing for 3 hours. Repeat the impregnation process 10 times to obtain a reinforced carbon / carbon composite material. 3) The 2123 thermosetting resin-reinforced carbon / carbon composite material was laminated and placed in a spark plasma sintering mold. During the spark plasma sintering process, the heating rate was 100℃ / min, the final sintering temperature was 1900℃, and the holding time was 30min; the cooling rate was 60℃ / min; and the axial pressure was 30MPa. The carbon / carbon composite material was obtained after spark plasma sintering.

[0037] The final low-density, high-strength carbon / carbon composite material has a density of 1.45 g / cm³ and a flexural strength of 63 MPa.

[0038] Example 3 The preparation method of the low-density, high-strength carbon / carbon composite material of the present invention includes the following steps: 1) Cut PAN-based carbon cloth into carbon cloth, ultrasonically clean and dry it. Then, acidify the dried carbon cloth with nitric acid, ultrasonically clean it and dry it again to obtain the treated carbon cloth. 2) The treated carbon cloth is impregnated with a polyimide solution, cured and dried to obtain a polyimide-reinforced carbon / carbon composite material; 3) After the polyimide-reinforced carbon / carbon composite material is stacked to the target thickness, it is placed in a mold and subjected to spark plasma sintering to obtain a low-density, high-strength carbon / carbon composite material.

[0039] In this embodiment, the ultrasonic cleaning time for both steps in step 1) is 5 minutes, and the drying is done in a 60°C oven.

[0040] In this embodiment, isopropanol is used as the solvent in the polyimide solution.

[0041] In this embodiment, the mass ratio of polyimide resin to solvent in the polyimide solution should be 1:1; In this embodiment, impregnation is performed under normal pressure, and the impregnation process ends when no bubbles are present.

[0042] In this embodiment, in step 2), during the curing and drying process, the standing time is 0.5h, the curing temperature is 60℃ and the curing time is 48h, the drying temperature is 60℃ and the drying time is 12h.

[0043] In this embodiment, during the spark plasma sintering process, the heating rate is 80℃ / min, the final sintering temperature is 1600℃, the holding time is 10min, the cooling rate is 10℃ / min, and the axial pressure is 10MPa.

[0044] In this embodiment, the carbon cloth is circular.

[0045] Example 4 The preparation method of the low-density, high-strength carbon / carbon composite material of the present invention includes the following steps: 1) Cut PAN-based carbon cloth into carbon cloth, ultrasonically clean and dry it. Then, acidify the dried carbon cloth with nitric acid, ultrasonically clean it and dry it again to obtain the treated carbon cloth. 2) The treated carbon cloth is impregnated with a polyimide solution, cured and dried to obtain a polyimide-reinforced carbon / carbon composite material; 3) After the polyimide-reinforced carbon / carbon composite material is stacked to the target thickness, it is placed in a mold and subjected to spark plasma sintering to obtain a low-density, high-strength carbon / carbon composite material.

[0046] In this embodiment, the ultrasonic cleaning time for both steps in step 1) is 30 minutes, and the drying is done in a 100°C oven.

[0047] In this embodiment, the solvent in the polyimide solution is deionized water.

[0048] In this embodiment, the mass ratio of polyimide resin to solvent in the polyimide solution should be 1:10; In this embodiment, vacuum impregnation is used, and the impregnation process ends when no air bubbles are present.

[0049] In this embodiment, when vacuum impregnation is used, the pressure is 0.01 kPa.

[0050] In this embodiment, in step 2), during the curing and drying process, the standing time is 2 hours, the curing temperature is 90°C and the curing time is 72 hours, the drying temperature is 90°C and the drying time is 36 hours.

[0051] In this embodiment, during the spark plasma sintering process, the heating rate is 250℃ / min, the final sintering temperature is 2000℃, the holding time is 60min, the cooling rate is 60℃ / min, and the axial pressure is 50MPa.

[0052] In this embodiment, the carbon cloth is circular.

[0053] Example 5 The preparation method of the low-density, high-strength carbon / carbon composite material of the present invention includes the following steps: 1) Cut PAN-based carbon cloth into carbon cloth, ultrasonically clean and dry it. Then, acidify the dried carbon cloth with nitric acid, ultrasonically clean it and dry it again to obtain the treated carbon cloth. 2) The treated carbon cloth is impregnated with a polyimide solution, cured and dried to obtain a polyimide-reinforced carbon / carbon composite material; 3) After the polyimide-reinforced carbon / carbon composite material is stacked to the target thickness, it is placed in a mold and subjected to spark plasma sintering to obtain a low-density, high-strength carbon / carbon composite material.

[0054] In this embodiment, the ultrasonic cleaning time for both steps in step 1) is 20 minutes, and the drying is carried out in a 70°C oven.

[0055] In this embodiment, the solvent in the polyimide solution is a combination of isopropanol and deionized water.

[0056] In this embodiment, the mass ratio of polyimide resin to solvent in the polyimide solution should be 1:8; In this embodiment, vacuum impregnation is used, and the impregnation process ends when no air bubbles are present.

[0057] In this embodiment, when vacuum impregnation is used, the pressure is 5 kPa.

[0058] In this embodiment, in step 2), during the curing and drying process, the standing time is 1 hour, the curing temperature is 80°C and the curing time is 60 hours, the drying temperature is 80°C and the drying time is 20 hours.

[0059] In this embodiment, during the spark plasma sintering process, the heating rate is 100℃ / min, the final sintering temperature is 1800℃, the holding time is 40min, the cooling rate is 40℃ / min, and the axial pressure is 30MPa.

[0060] In this embodiment, the carbon cloth is circular.

[0061] As can be seen from the above embodiments and comparative examples, under the same material system and impregnation conditions, carbon / carbon composite materials using different spark plasma sintering processes exhibit limited flexural strength, making it difficult to simultaneously achieve low density and high strength. However, using the process of this invention on carbon / carbon composite materials while keeping other conditions unchanged significantly improves the overall flexural strength, making it particularly suitable for large-scale engineering applications in fields such as aero-engine flame tubes, missile warhead fins, and high-temperature thermal protection skins.

[0062] Other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and disclosure of the invention. This application is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of the invention are indicated by the following claims.

[0063] It should be understood that the present invention is not limited to the precise structure described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.

[0064] The above description is merely a preferred embodiment of the present invention and does not constitute any limitation on the present invention. Any simple modifications, alterations, or equivalent structural changes made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a low-density, high-strength carbon / carbon composite material, characterized in that, Includes the following steps: 1) Cut PAN-based carbon cloth into carbon cloth, ultrasonically clean and dry it. Then, acidify the dried carbon cloth with nitric acid, ultrasonically clean it and dry it again to obtain the treated carbon cloth. 2) The treated carbon cloth is impregnated with a polyimide solution, cured and dried to obtain a polyimide-reinforced carbon / carbon composite material; 3) After the polyimide-reinforced carbon / carbon composite material is stacked to the target thickness, it is placed in a mold and subjected to spark plasma sintering to obtain a low-density, high-strength carbon / carbon composite material.

2. The method for preparing low-density, high-strength carbon / carbon composite material according to claim 1, characterized in that, In step 1), the ultrasonic cleaning time for both times is 5 min-30 min, and the drying is done in an oven at 60℃-100℃.

3. The method for preparing low-density, high-strength carbon / carbon composite material according to claim 1, characterized in that, The solvent in the polyimide solution is one or a combination of several of the following: isopropanol, deionized water, methanol, ethanol, propanol, n-butanol, isobutanol, n-hexane, n-pentanol, and isopentanol.

4. The method for preparing low-density, high-strength carbon / carbon composite material according to claim 1, characterized in that, The mass ratio of polyimide resin to solvent in the polyimide solution should be 1:(1-10).

5. The method for preparing low-density, high-strength carbon / carbon composite materials according to claim 1, characterized in that, Impregnation can be performed under normal pressure or under vacuum. The impregnation process ends when no air bubbles are present.

6. The method for preparing low-density, high-strength carbon / carbon composite materials according to claim 5, characterized in that, When vacuum impregnation is used, the pressure is 0.01-10 kPa.

7. The method for preparing low-density, high-strength carbon / carbon composite material according to claim 1, characterized in that, In step 2), during the curing and drying process, the standing time is 0.5-2 hours, the curing temperature is 60-90℃, the curing time is 48-72 hours, the drying temperature is 60-90℃, and the drying time is 12-36 hours.

8. The method for preparing low-density, high-strength carbon / carbon composite material according to claim 1, characterized in that, During the discharge plasma sintering process, the heating rate is 80-250℃ / min, the final sintering temperature is 1600-2000℃, the holding time is 10-60min, the cooling rate is 10-60℃ / min, and the axial pressure is 10-50MPa.

9. The method for preparing low-density, high-strength carbon / carbon composite material according to claim 1, characterized in that, The carbon cloth is circular.

10. A low-density, high-strength carbon / carbon composite material, characterized in that, It is prepared according to the preparation method of the low-density high-strength carbon / carbon composite material according to any one of claims 1-9.

Citation Information

Patent Citations

  • Multi-scale three-dimensional network carbon skeleton structure auxiliary composite material and preparation method thereof

    CN119263864A

  • 2.5 D woven carbon fiber preform reinforced Zr-based composite material and preparation method thereof

    CN119372567A